QualiAssistant: Extracting Qualia Structures from Texts - Manuel Biertz; Dumani Lorik; Markus Nilles; Björn Metzler; Ralf Schenkel (Proceedings of the 9th Workshop on Argument Mining, 2022)
In this paper, we present QualiAssistant, a free and open-source system written in Java for identification and extraction of Qualia structures from any natural language texts having many application scenarios such as argument mining or creating dictionaries. It answers the call for a Qualia bootstrapping tool with a ready-to-use system that can be gradually filled by the community with patterns in multiple languages. Qualia structures express the meaning of lexical items. They describe, e.g., of what kind the item is (formal role), what it includes (constitutive role), how it is brought about (agentive role), and what it is used for (telic role). They are also valuable for various Information Retrieval and NLP tasks. Our application requires search patterns for Qualia structures consisting of POS tag sequences as well as the dataset the user wants to search for Qualias. Samples for both are provided alongside this paper. While samples are in German, QualiAssistant can process all languages for which constituency trees can be generated and patterns are available. Our provided patterns follow a high-precision low-recall design aiming to generate automatic annotations for text mining but can be exchanged easily for other purposes. Our evaluation shows that QualiAssistant is a valuable and reliable tool for finding Qualia structures in unstructured texts.

The ReCAP Corpus: A Corpus of Complex Argument Graphs on German Education Politics. - Lorik Dumani; Manuel Biertz; Alex Witry; Anna-Katharina Ludwig; Mirko Lenz; Stefan Ollinger; Ralph Bergmann; Ralf Schenkel (ICSC, 2021)

Segmenting and Clustering Noisy Arguments. - Lorik Dumani; Christin Katharina Kreutz; Manuel Biertz; Alex Witry; Ralf Schenkel (LWDA, 2020)

The ReCAP Project. - Ralph Bergmann; Manuel Biertz; Lorik Dumani; Mirko Lenz; Anna-Katharina Ludwig; Patrick J. Neumann; Stefan Ollinger; Premtim Sahitaj; Ralf Schenkel; Alex Witry (Datenbank-Spektrum, 2020)